2015
DOI: 10.3892/ijo.2015.3201
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of eIF4E suppresses cell proliferation, invasion and enhances cisplatin cytotoxicity in human ovarian cancer cells

Abstract: Eukaryotic initiation factor 4E (eIF4E) plays an important role in cap-dependent translation. The overexpression of eIF4E gene has been found in a variety of human malignancies. In this study, we attempted to identify the potential effects of eIF4E and explore the possibility of eIF4E as a therapeutic target for the treatment of human ovarian cancer. First the activation of eIF4E protein was detected with m7-GTP cap binding assays in ovarian cancer and control cells. Next, the eIF4E-shRNA expression plasmids w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
(41 reference statements)
2
12
0
Order By: Relevance
“…It also has been demonstrated that a subset of mRNAs encoding cancer-associated proteins, such as c-MYC and cyclin D1, were identified to be sensitive to the activity of the eIF4F complex (15) and may serve as a convergence point for hyperactive signaling pathways to promote tumorigenesis (16). The present study confirmed that knockdown of eIF4E in GBC cells inhibited cell proliferation, oncogenic potential and cell cycle arrest, which is consistent with the previously described data (17,18).…”
Section: Discussionsupporting
confidence: 93%
“…It also has been demonstrated that a subset of mRNAs encoding cancer-associated proteins, such as c-MYC and cyclin D1, were identified to be sensitive to the activity of the eIF4F complex (15) and may serve as a convergence point for hyperactive signaling pathways to promote tumorigenesis (16). The present study confirmed that knockdown of eIF4E in GBC cells inhibited cell proliferation, oncogenic potential and cell cycle arrest, which is consistent with the previously described data (17,18).…”
Section: Discussionsupporting
confidence: 93%
“…GO analysis revealed that the OCC-1-repressed genes are mainly enriched for the regulators of gene expression that function at post-transcriptional and translational level ( 25 ). Meanwhile, many of these OCC-1-repressed genes have been found to directly involve in cancer cell growth, such as HNRNPA1 ( 47 ) and HNRNPK ( 48 ), which encode splicing factors, EIF3M ( 49 ) and EIF4E ( 50 ), which encode eukaryotic translation initiation factors, and mitotic division-associated genes MAD2L1 ( 51 ) and NEK2 ( 52 ). We reasoned that the upregulation of these genes is directly responsible for the increased cell growth in OCC-1 knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to Choi et al, eIF4e-positivity was associated with advanced tumour stage (III and IV) and reduced patient prognosis [21]. Other gynaecological malignancies, including cervical cancer [22][23][24][25], ovarian carcinoma [19,[26][27][28][29] and breast cancer [30][31][32], have been investigated more thoroughly regarding the prognostic, predictive and therapeutic relevance of eIFs. In cervical cancer, overexpression of eIF5a2 as detected by immunohistochemistry correlates with poor patient prognosis [25].…”
Section: Discussionmentioning
confidence: 99%